A method for cell type marker discovery by high-throughput gene expression analysis of mixed cell populations - Andrade-Navarro, Miguel A; Kanji, Femina; Palii, Carmen G; Brand, Marjorie; Atkins, Harold; Perez-Iratxeta, Carol (Université d'Ottawa | University of Ottawa, 2013)
Gene transcripts specifically expressed in a particular cell type (cell-type specific gene markers) are useful for its detection and isolation from a tissue or other cell mixtures. However, finding informative marker genes can be problematic when working with a poorly characterized cell type, as markers can only be unequivocally determined once the cell type has been isolated. We propose a method that could identify marker genes of an uncharacterized cell type within a mixed cell population, provided that the proportion of the cell type of interest in the mixture can be estimated by some indirect method, such as a functional assay.
Keywords: Cell markers; High-throughput gene expression; Cell isolation; Proof-of concept